Breast cancer induced nociceptor aberrant growth and collateral sensory axonal branching - Austin, Matt; Elliott, Laura; Nicolaou, Niovi; Grabowska, Anna M.; Hulse, Richard P. (Impact Journals, 2017)
The tumour and neuron interaction has a significant impact upon disease progression and the patients quality of life. In breast cancer patients, it is known that there is an interaction between the tumour microenvironment and the sensory neurons to influence the progression of cancer as well as pain, though these mechanisms still need to be clearly defined. Here it is demonstrated that in a rodent orthotopic model of breast cancer (MDA MB 231) there was an increase in nerve fibre innervation into the tumour microenvironment (protein gene product 9.5), which were calcitonin gene related peptide positive C fibre nociceptors. In contrast, there was a reduction in myelinated nerve fibres (NF200). A sensory neuronal cell line was cultured in response to conditioned media from MDA MB231 and MCF7 as well as vascular endothelial growth factor-A (VEGF-A). All these experimental conditions induced sensory neuronal growth, with increased formation of collateral axonal branches. Furthermore, it was demonstrated that MDA MB231 and VEGF-A induced sensory neuronal sensitisation in response to capsaicin a TRPV1 agonist. MDA MB231 induced neuronal growth was suppressed by VEGFR2 inhibition (ZM323881 and neutralising antibody DC101), in addition both MDA MB231 and VEGF-A induced neurite growth was attenuated by the inhibition of ARP2/3 complex through co-treatment with CK666. This demonstrates that breast cancer can interact with the sensory nervous system to drive neuritogenesis through a VEGF-A/VEGFR2/ARP2/3 mediated pathway.